The effect of classical music on balance, emotional state, and perceived effort in precompetitive artistic gymnasts and trampoline athletes - George Dallas; Costas Dallas; Eleni Stavropoulou; Dimitra Toli (Termedia Publishing House, 2024)
Purpose In artistic gymnastics (AG) and trampoline (TR ), athletes must be able to combine strength, flexibility, and artistry. The purpose of the study was to examine the effect of classical music on balance, emotional state, and perceived effort in precompetitive AG and TR athletes after a 6-week intervention training program. Methods The sample consisted of 36 athletes (20 AG and 16 TR athletes) who were randomly divided into two equal groups: experimental (with music) and control (without music). Balance ability was assessed with the Balance Error Scoring System (static balance) and the Y-balance test (dynamic balance). Before and after the intervention, participants completed the RPE-FS questionnaire which included a perceived fatigue scale (PFS) and an emotion scale (ES) to assess perceived fatigue (PF) and emotional state. The total sample followed a 6-week intervention training program, twice per week. TR athletes performed all exercises on a TR , whereas AG athletes performed their exercises on the floor. During the 6 weeks, the athletes completed the questionnaire before and after each training session. Results The results showed a statistically significant improvement in static and dynamic balance in female athletes of both sports ( p < 0.05), with the percentage of improvement in AG athletes being comparatively higher than that of TR athletes. There were also significant differences in individual measures of emotional state and perceived fatigue in the examined sample. Conclusions Classical music differentiates the rate of performance improvement in precompetitive young female athletes in these two sports.